2005
DOI: 10.1111/j.1365-3032.2005.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

High water‐loss rates and rapid dehydration in the burying beetle, Nicrophorus marginatus

Abstract: During the summer months, there is a high mortality of burying beetle (Coleoptera: Silphidae) species in pitfall traps containing dry soil. The present study investigated the possibility that the burying beetle Nicrophorus marginatus is highly susceptible to death from desiccation. In the laboratory, adult beetles lose 1-5% body mass per hour in low humidity conditions (25-30% relative humidity), depending on temperature. This rate of water-loss results in a 50% mortality within 7-16 h at temperatures between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…All four specimens were observed or collected within the first 3 days of succession. Drought conditions experienced throughout the central United States in 2002 appear to have reduced populations of Nicrophorus regionally (Bedick et al . 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four specimens were observed or collected within the first 3 days of succession. Drought conditions experienced throughout the central United States in 2002 appear to have reduced populations of Nicrophorus regionally (Bedick et al . 2006).…”
Section: Resultsmentioning
confidence: 99%
“…All four specimens were observed or collected within the first 3 days of succession. Drought conditions experienced throughout the central United States in 2002 appear to have reduced populations of Nicrophorus regionally (Bedick et al 2006). One other species of silphid beetle, Thanatophilus lapponicus Herbst, was represented by three specimens collected only within the first 2 days of succession.…”
Section: Successionmentioning
confidence: 99%
“…From the current findings, the antimicrobial activity of the beetles' oral secretions is most active at temperatures below 20°C. Bedick et al (2006) reported a 50% mortality rate due to water loss for N. marginatus beetles when kept above 20°C in low humidity conditions for 10 h.…”
Section: Different Letters Represent a Significant Difference Betweenmentioning
confidence: 97%
“…Lab studies have suggested that N. americanus prefer moist soils (W. W. Hoback, unpubl. data), and other members of the genus Nicrophorus can be extremely susceptible to dessication (Bedick et al ., ). Although they are hypothesised to be associated with moist soils, burying beetles must avoid flood prone areas to prevent inundation of their underground brood chambers.…”
Section: Methodsmentioning
confidence: 97%
“…Temperature is likely the most important determinant of flight activity with upper and lower bounds beyond which flight activity is reduced or physiologically impossible (Taylor, ; Merrick & Smith, ). Due to the susceptibility of burying beetles to desiccation (Bedick et al ., ; Bedick et al ., D. Leasure, pers. obs.…”
Section: Introductionmentioning
confidence: 99%